2006
DOI: 10.1021/ef060188t
|View full text |Cite
|
Sign up to set email alerts
|

Argonne Coal Structure Rearrangement Caused by Sorption of CO2

Abstract: The exposure of powdered unconfined coals to CO 2 results in changes in the coals' physical structures. The presence of water changes the behavior of the coals on exposure to CO 2 . The sorption of CO 2 on seven Argonne premium coals was measured by using attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy as a function of time at constant CO 2 pressure (∼0.62 MPa) and temperature (55 °C). The depth sampled is at least 1 µm, and this ensures that both the bulk and surface of the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…Our equilibration time is much longer than the one reported in Table 4, apart for Majewska et al (2009) who was working with coal blocks and Goodman et al (2006) who plotted pressure decrease versus the squared root of time.…”
Section: Equilibration Time For the Sorption Experimentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Our equilibration time is much longer than the one reported in Table 4, apart for Majewska et al (2009) who was working with coal blocks and Goodman et al (2006) who plotted pressure decrease versus the squared root of time.…”
Section: Equilibration Time For the Sorption Experimentsmentioning
confidence: 97%
“…The equilibration time depends on gas, temperature of the system and the grain sizes of coal used in the experiments. A few authors studied the kinetics of the gas sorption on coal (Clarkson and Bustin, 1999b;Siemons et al, 2003;Busch et al, 2004;Solano-Acosta et al, 2004;Goodman et al, 2006;Gruszkiewicz et al, 2009). CH 4 and CO 2 adsorption occurs much faster in fine grained fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Currently there are gaps in our fundamental understanding of coal interactions with adsorbates such as the kinetics of gas transport through the coal matrix and the swelling/ shrinkage response of coal as adsorbates are introduced and removed. Native coal, defined here as coal possessing its inherent moisture as received with minimal handling and treatment, is considered to be in a strained glassy state with the potential for structural rearrangements upon exposure to CO 2 (Larsen, 2004;Goodman et al, 2005Goodman et al, , 2006. Initial exposure of briefly dried coal to CO 2 leads to physical structural rearrangement (Goodman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Native coal, defined here as coal possessing its inherent moisture as received with minimal handling and treatment, is considered to be in a strained glassy state with the potential for structural rearrangements upon exposure to CO 2 (Larsen, 2004;Goodman et al, 2005Goodman et al, , 2006. Initial exposure of briefly dried coal to CO 2 leads to physical structural rearrangement (Goodman et al, 2006). Significant differences in acoustic emission signal between the first and subsequent adsorption cycles provides further evidence of structural rearrangements during the first CO 2 adsorption cycle for dried coal (Majewska and Zietek, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The imbibition or dissolution of carbon dioxide, a powerful coal plasticizer, results in the physical structure relaxation and rearrangement (Larsen, 2004;Goodman et al, 2006). Larson and co-workers suggested that rearrangement will induce substantial increase in the self-diffusivity of CO 2 in the coal matrix, although it also appears that as the structure undergoes volumetric relaxation, the excess free volume associated with the glassy state is reduced, resulting in lower diffusion (Duda et al, 1994).…”
Section: Introductionmentioning
confidence: 99%